Bridges of hope: IBBY Ireland projects for a changing population. Issue 1 (1st April 2022) - Thomas, Debbie; Feeney, Tatyana
Migration and storytelling are defining and entwined features of humanity. Throughout history, people have travelled, in body and mind, exploring new places and ideas either by choice or necessity. Migration establishes cultural connections and imaginative possibilities, like new neural pathways in the collective human brain. This article explores workshops, designed and run in Ireland by children's author Debbie Thomas and children's author and illustrator Tatyana Feeney, who have used creative writing and illustration to build bridges between immigrants and Irish nationals, mainly children. We will describe cross-cultural workshops we have facilitated with children around Ireland and then focus on three major projects: Once upon a Folktale and Nation Creation (with children in mainstream Irish primary schools) and Connections (with Syrian refugees). In each project, Debbie oversaw the writing and Tatyana, the illustrations. All three projects have bridged cultures and enriched young participants, teachers and facilitators both culturally and creatively.